EFEKTIVITAS KONSELING INDIVIDUAL DENGAN PENDEKATAN REBT DALAM MENGURANGI PERILAKU AGRESIF ANAK BINAAN DI LPKA KELAS II SUNGAI RAYA - Putri, Inna Rehamni; M.Asrori; Putri, Amallia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2026)
This study aims to determine the effectiveness of individual counseling using the Rational Emotive Behavior Therapy (REBT) approach in reducing aggressive behavior among foster children at LPKA Class II Sungai Raya. The research method employed is an experimental design with a Pre-test-Post-test One Group approach. The sample was selected using a purposive sampling technique. namely 4 children out of 20 foster children who had high levels of aggression. Before being given counseling services, the average aggressive behavior score of children was 185. After being given counseling using the REBT approach, the score decreased to 140.75. Data analysis using the Paired Sample T-test showed a t-test value of 5.083 with a significance value of 0.000 (p